Exploration of Gresik Local Wisdom (Tegal Deso-Okol) as Student Learning Resources on Environmental Pollution to Build Awareness of Cultural Values - Diah Dwi Firnanda; Mahanani Tri Asri; Ulfi Faizah (Indonesian Journal of Educational Science (IJES), 2025)
The exploration of local wisdom integrated into education has great potential to increase students' awareness of the importance of environmental conservation, especially in dealing with pollution problems. This study aims to explore local wisdom (Tegal Deso-Okol) in Gresik and analyze its role in environmental conservation and its potential as a learning resource for students on environmental pollution material. The research method used was a survey to identify local wisdom, traditions, and practices relevant to biology learning. The research process involved interviews with local people, migrants, as well as officials and community leaders to explore information about habits, phenomena, culture, and beliefs in a series of events (Tegal Deso-Okol). The results showed that local wisdom in Setro Village and Bongso Wetan Village reflected a close relationship as a form of respect for nature and ancestors. The values contained in the local wisdom include 1) religious value, 2) environmental value, 3) trust value, 4) sharing value, 5) cultural value, and 6) tradition preservation value. Gresik's local wisdom also serves as a learning resource, where the use of natural materials from cultural activities, such as food waste and straw waste, is developed into compost as organic fertilizer.